Evaluation of the antimicrobial activity of novel composite plastics containing two silver (I) additives, acyl pyrazolonate and acyl pyrazolone - Scuri, Stefania; Petrelli, Fabio; Grappasonni, Iolanda; Idemudia, Loveth; Marchetti, Fabio; Di Nicola, Corrado (Acta Biomedica Atenei Parmensis, 2019)
Background: Public health systems today face the dual challenges of controlling infections and curbing the increase in antimicrobial resistance manifested in drug-resistant microorganisms in hospitals and elsewhere. In the last ten years, research has been conducted to develop new materials with antimicrobial properties to be used in medical devices, increasingly found to harbour critical nosocomial infections. Methods: Two next-generation composites using the antimicrobial qualities of silver were tested against Escherichia coli, Staphylococcus aureus and Candida albicans with the purpose of evaluating their antimicrobial and antifungal activity. These tests applied the standardized method according to ISO-2216: Plastics-Measurement of Antibacterial Activity on Plastics Surfaces. Testing was carried out using polyethylene (PE) enriched with AgNO3 as a positive control and PE as a negative control. Results: The antimicrobial activity of the composites proved to be between medium (bacteriostatic) and very good (bactericidal). In particular, PE2 showed the highest scores against all microorganisms, with values ranging from good to very good. Instead, PE1 had lower scores, with a value of medium for Escherichia coli and slight for Candida albicans. Statistical analysis carried out with the t-test for unpaired data showed a statistically significant difference between the positive control and the other polymers (p< .0001). Conclusions: Based on our findings, we conclude that the test, conducted to ISO-2216 standards, could be extended to include fungal strains and that the new composites could be used to produce antimicrobial surfaces for medical devices, for example, intubation tubes, urinary catheters, vascular prostheses, and mechanical heart valves. This would reduce the risk of microbial contamination and biofilm formation, ensuring better health outcomes for patients treated with these devices. Further testing should be done to evaluate potential future applications of these composites and the possibility of adding fungal strains to the IS0-2216 standard.